ANALISIS PENGARUH RELIGIUSITAS DAN BUDAYA TERHADAP PEMAHAMAN MASYARAKAT MENGENAI SERTIFIKASI PRODUK HALAL DI KECAMATAN PAMIJAHAN DAN KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Muhamad Syahrulludin; Ermi Suryani; Bayu Purnama Putra (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
Information circulating about halal certification for products can change the pattern of purchasing activities of the public, who initially did not really care about products labeled halal to care about the importance of products labeled halal. The purpose of this study was to determine the effect of religiosity and culture on people's understanding of halal product certification. This type of research is quantitative. The analytical method used is multiple linear regression analysis using SPSS version 25. The results of this study indicate that religiosity and culture together have a real and positive influence on people's understanding of halal product certification. This is reflected in research that is located in Pamijahan District and Cibungbulang District, Bogor Regency. Increasing the understanding of religiosity and culture in the community can encourage an increase in the development of understanding of halal product certification in the community.